2019
DOI: 10.1002/jcp.28445
|View full text |Cite
|
Sign up to set email alerts
|

The role of BAFF and APRIL in rheumatoid arthritis

Abstract: Development and activation of B cells quickly became clear after identifying new ligands and receptors in the tumor necrosis factor superfamily. B cell–activating factor (BAFF) and a proliferation‐inducing ligand (APRIL) are the members of membrane proteins Type 2 family released by proteolytic cleavage of furin to form active, soluble homotrimers. Except for B cells, ligands are expressed by all such immune cells like T cells, dendritic cells, monocytes, and macrophages. BAFF and APRIL have two common recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 145 publications
(189 reference statements)
2
50
0
1
Order By: Relevance
“…Our results were concordant with earlier reports demonstrating high serum APRIL levels in serum and synovial tissue of RA patients [23,24]. Our results could be explained on the basis that in the early phase of RA disease, the APRIL is produced signi cantly by dendritic cells, which leads to an increase in the proliferation of B cells; and ultimately, B cells are differentiated by APRIL producing autoantibodies [25]. Macrophages, on the other hand, are considered to be the source of APRIL in the con rmed phase of the disease [26], causes the accumulation of plasma cells in the joint, further increasing the production of in ammatory cytokines such as TNF, IL-1, and IL-6 [18].…”
Section: Discussionsupporting
confidence: 93%
“…Our results were concordant with earlier reports demonstrating high serum APRIL levels in serum and synovial tissue of RA patients [23,24]. Our results could be explained on the basis that in the early phase of RA disease, the APRIL is produced signi cantly by dendritic cells, which leads to an increase in the proliferation of B cells; and ultimately, B cells are differentiated by APRIL producing autoantibodies [25]. Macrophages, on the other hand, are considered to be the source of APRIL in the con rmed phase of the disease [26], causes the accumulation of plasma cells in the joint, further increasing the production of in ammatory cytokines such as TNF, IL-1, and IL-6 [18].…”
Section: Discussionsupporting
confidence: 93%
“…A recent trial called ROSE aiming to explore the effectiveness of abatacept in RA-SS justifies the crosstalk of T cells between the two diseases [40]. Additionally, B cells are considered as central actors of SS pathogeny, and excess B cell activating factor (BAFF) level is likely to mediate autoreactive B cell accumulation [41], while in the pathogenesis of RA, B cells are involved mainly by producing autoantibodies targeted citrullinated proteins [42]. Previous studies have shown that elevated BAFF levels were positively correlated with RF/ACPA and radiographic progression in RA patients [43][44][45].…”
Section: Adaptive Immune Systemmentioning
confidence: 99%
“…Our results were concordant with earlier reports demonstrating high serum APRIL levels in serum and synovial tissue of RA patients (Tayel et al 2013 ; Boghdadi et al 2015 ). Our results could be explained on the basis that in the early phase of RA disease, the APRIL is produced significantly by dendritic cells, which leads to an increase in the proliferation of B cells; and ultimately, B cells are differentiated by APRIL producing autoantibodies (Shabgah et al 2019 ). Macrophages, on the other hand, are considered to be the source of APRIL in the confirmed phase of the disease (Ancuta et al 2017 ), causes the accumulation of plasma cells in the joint, further increasing the production of inflammatory cytokines such as TNF, IL-1, and IL-6 (Zhao et al 2014 ).…”
Section: Discussionmentioning
confidence: 87%